ROMANIA AND THE EUROPEAN UNION ENLARGEMENT - Hoek, M. Peter Van Der (Journal of European Economy, 2017)
The article considers the issues of Romania's membership in the EU. The author compares the EU’s «Eastern» enlargement of 2004 with previous enlargements. As it turns out, the EU becomes poorer with every next enlargement: its per capita GDP decreases every time compared with per capita GDP of the six constitutor countries (Belgium, France, Germany, Italy, Luxemburg, and Netherlands). There are also sufficient economic arguments for postponement of Romania's accession in 2007 (or 2008). Romania does not exhibit the same macroeconomic stability the other countries of south-eastern Europe do; its welfare is lower, and its progress in building market economy is slower compared to the countries that joined the EU in 2004. Moreover, Romania achieved little progress in fighting corruption. Finally, the author discusses the consequences of the rejection of the EU constitution by the French and the Dutch in 2005. In view of the ratification problems, five options are suggested as possible solutions to the problems. The most probable is that the EU will proceed on the basis of the Nice treaty and political agreements. Further enlargement of the EU will be much more difficult to realize than in the past. This does not apply to Bulgaria and Romania, since the accession treaties were already signed in 2005, and they will join the EU in 2007 or 2008. However, this does apply to Croatia and Turkey, with whom the EU opened accession negotiations in October 2005.